SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS OF TEACHING THEORETICAL AND PRACTICAL CONCEPTS IN TEACHING THE SUBJECT "TECHNOLOGY" IN PRIMARY EDUCATION - Abdullayeva Zilola Erkin qizi (Bright Mind Publishing, 2026)
This article examines the scientific and methodological foundations of teaching theoretical and practical concepts in the subject “Technology” in primary education. The study highlights the importance of integrating theory with practice to develop pupils’ technological literacy, creative thinking, and practical skills from an early age. Attention is given to modern pedagogical approaches, including competency-based education, activity-oriented learning, and the use of interactive and project-based methods in technology lessons. The paper also analyzes the role of age-specific characteristics of primary school learners, the selection of appropriate teaching methods and tools, and the application of didactic principles in ensuring effective learning outcomes.
Keywords: Primary education, technology subject, scientific foundations, methodological approaches, theoretical and practical concepts, competency-based learning, practical skills, creative thinking.